Bimbingan Teknik Komunikasi dan Koordinasi Pengurus dengan Anggota Koperasi Binaan Integrated Corporation of Agricultural Resources Empowerment (ICARE) di Kabupaten Garut - Purnamawati, Ami (E-Coops-Day, 2024)
An implemented program of Integrated Corporation of Agricultural Resources Empowerment (ICARE) of West Java was technical counselling of cooperative management for cooperatives boards in Garut Regency. It was a collaborated program with the institution of research and community service (LPPM) of Universitas Koperasi Indonesia (Ikopin University). For this program, the development of new cooperatives was focused on the deepening comprehension of cooperative characteristics of both organization and business. The trainer team designed three topics “why cooperative”, “managing cooperative business” and “assessing cooperative and action commitment”. The program was one day training and there were three trainers for three topics. The first topic ‘why cooperative” consisted of the cooperative identity explaining the definition, values, and principles of cooperative as well as the benefits of it. The topic was related to communication and coordination among cooperative boards and its members as the keys in achieving cooperative goals. The method used were icebreaking, lecturing, and discussion. The participants of the program were the boards of new cooperatives having agriculture and farming business. They had various background of experiences, education and ages. The participants’ feedback showed positive attitudes toward the programs, topics as well as the trainers indicated by the interactive process during the program and the conducive situation.